Transformasi Industri Pelayaran Global Pasca COVID-19: Tinjauan Empat Pasar Utama - Qunfayakun Adam; Eliyanti Agus Mokodompit (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study examines the impact of the post-COVID-19 global trade recovery on the four principal markets of the shipping industry: the freight market, second-hand ship market, newbuilding market, and ship demolition market. Employing a literature review approach, the study synthesizes recent academic and industry evidence to identify structural changes that emerged during and after the pandemic. The findings indicate that COVID-19 generated significant disruptions across global supply chains, leading to operational inefficiencies, port congestion, fluctuating demand patterns, and unprecedented increases in charter rates. As international trade gradually recovered, the shipping industry experienced notable market adjustments. The newbuilding market expanded in response to renewed trade demand and fleet modernization requirements, while the second-hand ship market exhibited substantial price volatility driven by shifting market expectations and capacity constraints. Simultaneously, the demolition market was influenced by cyclical freight conditions and increasingly stringent environmental regulations aimed at reducing emissions and promoting sustainable shipping practices. The study further reveals that national and international regulatory frameworks have played a critical role in accelerating efficiency improvements, enhancing maritime safety, and supporting industry-wide decarbonization efforts. Overall, the post-pandemic recovery has not merely restored shipping activities but has also transformed the industry's operational and strategic landscape. The shipping sector is increasingly characterized by digitalization, resilience-oriented management, environmental sustainability, and adaptive market mechanisms. These findings contribute to a broader understanding of how global crises reshape maritime markets and provide insights for policymakers, industry stakeholders, and researchers seeking to navigate the evolving dynamics of the global shipping industry.